Meningkatkan Pemahaman Siswa Tentang Komponen Penyusun Atap Melalui Media 3D Sketchup dan Maket - Lugita Sari, Prisillia; Wanarti Rusimamto, Puput; Anifah, Lilik; Asto Buditjahjanto, I Gusti Putu (Educatio, 2025)
The use of teaching aids in implementing learning can arouse new desires and interests in learning, arouse motivation and learning stimuli, and bring psychological influences to students. This study aims to improve students' understanding of roof components through 3D Sketchup and teaching aids. The research in the first and second cycles was conducted in one meeting, including planning, implementation, observation, and reflection. The collection of information about students' understanding was obtained by providing a questionnaire of students' responses to the understanding of roof truss objects quantitatively. The results of the questionnaire given to students regarding the understanding of imagining real objects in roof truss construction before learning, 52.94% chose scale 1 (very much do not understand) and 47.06% chose scale 2 (do not understand). While the results of the questionnaire given to students regarding the understanding of imagining real objects in roof truss construction after learning, 58.82% chose scale 4 (understand) and 41.18% chose scale 5 (very much understand). Based on the results obtained, the use of 3D sketchup and roof models can improve students' understanding of the components of the roof.